THE INFLUENCE OF THE EXPERIENCE OF DIGITAL NOMAD TOURISTS ON DESTINATION LOYALTY IN CANGGU, BADUNG DISTRICT, BALI - Handizar, Dhyana Hanifianti; Sumaryadi; Suteja Wira Dana Kusuma (International Journal of Sustainable Competitiveness on Tourism, 2023)
Nomadic tourism fills the gap between a strategy to increase number of tourist and the development of information and communication technology which makes everyone be able to live and working any where as long as they’re connected to the internet. People who are processing their professional activities while having a migrating lifestyle with high mobility are defined as Digital Nomad. Which in Nomadic Tourism terminology, Digital Nomad counts as one of the type of Nomadic tourist as well. Hence, the appearance of Digital Nomad not only relevant in the growing of living and working environment but also relevant in tourism trend. The presence of digital nomad needs to be highlighted since Indonesia, precisely in Canggu, Bali chosen as number one destination for digital nomad. Even so, destination loyalty from digital nomad’s perspective in Canggu is indicated has a low level, therefore it is needed to see if tourist experience is taking part in this since tourist experience is one of the crucial factors that can affect destination loyalty, besides digital nomad has a characteristic to prioritize their experience. The purpose of this study is to display digital nomad’s tourist experience, destination loyalty, and how their experience affects their destination loyalty in Canggu. The method that is used on this study is descriptive quantitative. The result from this study is digital nomad’s tourist experience and destination loyalty are in a good category, and there’s a significant influence from digital nomad’s tourist experience to their destination loyalty in Canggu. A step that can be done by the destination is to explore and increase the distinction value in Canggu